Biodegradation of petroleum oil by using Isolated Penicillium sp. / Nabilah Razak, Saiyidah Nafisah Hashim and Chia Chay Tay - Nabilah, Razak; Saiyidah Nafisah, Hashim; Chia, Chay Tay (2015)
he biological solutions have become more familiar to remove hazardous substances from the environment. This present investigation was conducted in order to isolate fungi from contaminated soil collected from workshop area near Arau, Perlis. These isolated fungi were then tested on their ability to degrade petroleum oil on PDA medium that was polluted with different concentration of petroleum oil 2%,4% and 10% (v/v) and on the minimal salt solution by measuring changes in optical density (OD) read on spectrophotometer with 540 nm wavelength. Penicillium sp. was isolated from the contaminated soil using soil serial dilution method. Penicillium sp. was capable of actively degrade in varying degrees. The result showed significant difference (P<0.05) between different concentration of oil and the growth of fungi in 5 days of incubation period at 2% and 10% (v/v) petroleum oil concentration. Penicillium sp. showed highest growing diameter in 4% concentration of petroleum oil. Based on the optical density result, Penicillium sp. showed maximum peak of OD reading in day 20 with 0.66 ± 0.01, indicate that the highest ability of Penicillium sp. to degrade petroleum oil were in day 20. Statistical analysis of one-way ANOVA was done. The ability ofPenicillium sp. to tolerate oil pollutants and grow on them, suggest it can be employed as bioremediation agent and can be used in restoring contaminated ecosystem with oil.